2019
DOI: 10.31676/0235-2591-2018-6-40-46
|View full text |Cite
|
Sign up to set email alerts
|

Problems and prospects of development of horticulture in Russia

Abstract: In Russia, about 25 kg of fruit per year is produced per capita, which is 75 % of the rational norm of nutrition. In the domestic agri-food market, more than 70 % are imported fruits. At the present stage, a negative trend in the development of horticulture is the reduction of areas under fruit and berry crops. For 2000-2017 their total area decreased by 250 thousand hectares, or by 32.1 %. A signifi cant increase in the yield of orchards and berry fi elds (88.9 percent) during the reduction of surface area di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Food resources are one of the main concerns of food security worldwide. A country will achieve food independence if it manages to produce food products domestically more than the amount needed by the people (Kulikov and Minakov, 2019). Research has found that the factors that affect the food resources nationally and globally are climate change, population growth, and economic development (Radulescu et al, 2020).…”
Section: Impact Of Food Safety Regulations Implementation On Food Res...mentioning
confidence: 99%
“…Food resources are one of the main concerns of food security worldwide. A country will achieve food independence if it manages to produce food products domestically more than the amount needed by the people (Kulikov and Minakov, 2019). Research has found that the factors that affect the food resources nationally and globally are climate change, population growth, and economic development (Radulescu et al, 2020).…”
Section: Impact Of Food Safety Regulations Implementation On Food Res...mentioning
confidence: 99%
“…Failure to realize these products in time thus results in large losses. Dairy farming is a less profitable industry compared to the production of grain, sugar beets, sunflowers, etc., with a long payback period of investment (more than 10 years), which makes it less attractive for investment (Kulikov and Minakov, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The yield of berry plantations requires a modern development of measures system to develop the production of Goji berries. The development of berry production implies the following: the use of high-quality healthy planting material, the use of high-yielding species with good taste and transportable qualities of berries, the use of protection of berry plantations from diseases and pests, the use of rational and efficient irrigation [13,14,15,16]. The development of Goji berries production on an innovative basis should be carried out with the state support of the industry [17,18,19].…”
Section: Introductionmentioning
confidence: 99%